2005
DOI: 10.1107/s0108768105008116
|View full text |Cite
|
Sign up to set email alerts
|

Local structural properties of (Mn,Fe)Nb2O6 from Mössbauer and X-ray absorption spectroscopy

Abstract: The MnNb 2 O 6 -FeNb 2 O 6 solid solution has been investigated by Fe-K-and Mn-K-edge X-ray absorption (XANES and EXAFS), and Mö ssbauer spectroscopy. The first-shell M-O bond lengths deduced from EXAFS show a fairly small compositional dependence. A degree of static disorder, which increases with increasing manganese content, is clearly seen by the loss of correlation for the next-neighbour (NN) interaction. Hyperfine parameters from Mö ssbauer spectra are consistent with variations in the average environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…This disorder effect on the diffraction patterns is fully described in Guinier’s textbook . It has been confirmed by the complementary diffraction and EXAFS studies of various materials such as metallic alloys, , metallic oxides, and lamellar compounds. , As in our case, all these materials are solid solutions. Their XRD refinements lead to linear variations of crystal lattices versus composition.…”
Section: Resultssupporting
confidence: 79%
“…This disorder effect on the diffraction patterns is fully described in Guinier’s textbook . It has been confirmed by the complementary diffraction and EXAFS studies of various materials such as metallic alloys, , metallic oxides, and lamellar compounds. , As in our case, all these materials are solid solutions. Their XRD refinements lead to linear variations of crystal lattices versus composition.…”
Section: Resultssupporting
confidence: 79%
“…In the case of the series of naturally occurring (Fe x Mn 1− x )(Ta y Nb 2− y )O 6 , site mixing between Mn and Fe O h sites in the TaO 6 and NbO 6 was found when neutron and PXRD refinements were combined. 14 Tarantino et al 20 showed for a series of (Mn,Fe)Nb 2 O 6 that the EXAFS data have small composition dependence in the first shell (metal–oxygen bond lengths from Mn K- and Fe K-edges), which suggests that differences between the local structure of an ordered or disordered MNO would be minor, and it agrees with the observations here made.…”
Section: Resultssupporting
confidence: 88%
“…The structure of the mineral columbite (Fe,Mn)(Nb,Ta) 2 O 6 and annealed samples have been investigated through combining laboratory X-ray and neutron diffraction refinements and 57 Fe Mössbauer spectroscopy. 14,19,20 These studies concluded that interlayer mixing between A and B exists. In the extreme case the ixiolite structure is observed.…”
Section: Introductionmentioning
confidence: 99%
“…The families of oxide compounds with the general formula AB 2 O 6 (A-Fe, Mn, Mg, Zn, Ca, Co, Ni; B-Ta, Nb, V, Pb) have attracted much interest because of their important use in technological applications. The high permittivity and low dielectric loss at microwave frequencies make these materials suitable for use as resonators in the fields of satellite communications, supercapacitors in electric cars, ceramics in microwave technology, and many other electric devices. The AB 2 O 6 compounds are also used as important intermediates for the synthesis of perovskite structure related materials . Among AB 2 O 6 compounds, (Mn,Fe)­(Nb,Ta) 2 O 6 with A and B sites mainly occupied by Mn 2+ or Fe 2+ and Ta 5+ or Nb 5+ , respectively, deserves special attention due to its potential applications …”
Section: Introductionmentioning
confidence: 99%